Gold and silver complexes of BIS (phosphino) hydrazine ligands as potential anti-tumour agents - Kriel, Frederik Hermanus (My University, 2008)
Cancer is presently responsible for about 25 % of all deaths in developed countries. It has a substantial impact on a patient's quality of life and many cancer treatments (such as chemotherapy) may have severe side-effects. New therapies that display a minimum of the drastic side-effects of current drugs are constantly sought after. The first comprehensive studies of the anti-tumour potential of gold compounds, including gold drugs, were published in the mid-to-late 1980’s. Gold(I) bisphosphine compounds of bis(diphenylphosphino)ethane (dppe) and related ligands with a tetrahedral coordination geometry turned out to be a particularly potent class of compounds. Clinical trials were, however, not pursued owing to the acute toxicity associated with them. The high toxicity of [Au(dppe)2]+ is attributable to the high lipophilicity of the cations which results in non-selective uptake into mitochondria in all cells. The tumour selectivity of tetrahedral gold(I) complexes was found to hinge on a fine balance between its lipophilic and hydrophilic character. One way of introducing the more hydrophilic character to a ligand or complex, necessary for selectivity, is the addition of heteroatoms. To this end, one of the aims of this project was to synthesise a range of ligands where the lipophilic ethane bridge of dppe was replaced by a hydrazine bridge. It was hoped that the addition of the nitrogen heteroatoms would increase the hydrophilic character of the ligands, thus rendering more selective drug candidates. Further modifications identified included the initial phenyl substituents on the phosphorous centres could be enriched by replacing the phenyl with either O-methylanisol or N,N-dimethylaniline. In both cases four extra heteroatoms per ligand were added, oxygen in the case of anisol and nitrogen in the case of aniline. With dimethylhydrazine or diethylhydrazine as starting material six ligands were synthesised and characterised. Crystallisation efforts afforded a x-ray crystal structure of bis(diphenylphosphino)diethylhydrazine. In contrast to the stability of the diethylhydrazine ligands, the dimethylhydrazine ligands were found to be prone to decomposition, at times even under an inert atmosphere. The aim of AuTEK Biomed is the inclusion of metals, in this case gold(I) and silver(I), to the above mentioned ligands (L) to enhance activity. To this effect, six phosphine-bridged gold complexes (ClAu-L-AuCl), six bischelated gold complexes (AuL2Cl), six phosphine-bridged silver complexes (NO3Ag-L-AgNO3) and six bischelated silver complexes (AgL2NO3) were attempted. It was found that the ClAu-L-AuCl complexes are very stable and readily crystallise from THF. Five of the six complexes could be characterised by x-ray crystallography. The sixth complex, that of bis(di(N,N-dimethylanaline)phosphino)dimethylhydrazine, could not be isolated due to the breakdown of the ligand upon addition of the metal starting material. Succesful preparation of five of the six AuL2Cl complexes was accomplished. These complexes where found to be slightly hygroscopic and storage under an inert atmosphere was required. Efforts to crystallise these complexes led to the crystallisation of conglomerates of micro crystals, which could not be analysed crystallographicly due to the disordered nature of the micro crystals. The synthesis of the bischelated gold complex of bis(di(N,N-dimethylanaline)- phosphino)diethylhydrazine led to an interesting phenomenon which was studied further. Upon complexation, the expected yellow complex spontaneously turned bright red even when the solvent was removed. Efforts to crystallise this complex was not successful until the counter ion (Cl-) was replaced with that of NO3 -. The crystal structure revealed that gold(I) had spontaneously oxidised to gold(III) and this crystal structure represents the first known complex to our knowledge of gold(III) chelated to four phosphorous centres. NO3Ag-L-AgNO3 complexes were mostly unstable and regularly led to the formation of a silver mirror on the reaction vessel. Even with this inherent instability of these complexes, it was possible to characterise three of the complexes to some extent and to analyse the complex of bis(diphenylphosphino)diethylhydrazine by x-ray crystallography. The molecular structure showed intricate connectivity between the complexes leading to polymeric structures. The tetrahedral silver complexes were markedly more stable and five of the complexes could be isolated and characterised. The molecular structure of bis(bis(diphenylphosphino)diethylhydrazine)silver nitrate could be determined.Thirteen of the complexes were found to be sufficiently stable to be investigated as potencial drug candidates and were subjected to in vitro anti-tumour screening. These thirteen complexes were firstly screened against three cell lines, namely the cancerous HeLa and Jurkat cell lines and Lymphocytes obtained from healthy human donors. These results were analysed and selectivity for toxicity towards cancerous cell-lines vs the healthy cell line was calculated. Five complexes were identified as suitable for investigation on a further range of cell lines based on the specificity they displayed. Two of the complexes were of the type ClAu-L-AuCl, while the other three were of the type AgL2NO3. The five compounds were screened against A2780, A2780cis, Colo, MCF-7 and MCF-12 cell lines from which new selectivity profiles were calculated. Due to the mechanism of activity of [Au(dppe)2]+ being described as apoptosis induced through the disruption of mitochondrial membrane potential, so leading to cell arrest, it was decided to test whether these analogues would work through the same mode of action. To this end, the best two complexes, namely ClAu(MeO-4- Ph)2PN(Et)N(Et)P(Ph-4-OMe)2AuCl and [{(MeO-4-Ph)2PN(Me)N(Me)P(Ph-4- OMe)2}2 Ag]+.NO3 -, selected through the analysing of selectivity calculations were subjected to the mitochondrial membrane potential and apoptosis assays. From the mitochondrial membrane potential assay it could be proven that these complexes do indeed affect the mitochondrial membrane potential by lowering the potential necessary to the cell for producing ATP. Results from the apoptosis assays were inconclusive and remain as future work. The hypothesis of this theses is that it is possible to fine tune the lipophilic/hydrophilic balance of tetrahedral Group 11 complexes to improve selectivity towards cancerous cells above healthy cells. This has to a certain extent been proven through the increased selectivities of these complexes when compared to [Au(dppe)2]+. It has to be mentioned that even though increased selectivities are observed for these complexes, the selectivities are not profound enough to merit further investigation into the anti-tumour activity of these complexes.